2015
DOI: 10.1108/imds-08-2014-0231
|View full text |Cite
|
Sign up to set email alerts
|

The effects of convenience and speed in m-payment

Abstract: Access to this document was granted through an Emerald subscription provided by 405387 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
222
2
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 338 publications
(258 citation statements)
references
References 69 publications
28
222
2
6
Order By: Relevance
“…We also examined the normality of the data distribution with skewness and kurtosis. All skewness and kurtosis are less than 3 and 10 respectively (Teo, Tan, Ooi, Hew, & Yew, 2015). Hence, we concluded that the data is normally distributed.…”
Section: Test Of Multivariate Assumptionsmentioning
confidence: 64%
“…We also examined the normality of the data distribution with skewness and kurtosis. All skewness and kurtosis are less than 3 and 10 respectively (Teo, Tan, Ooi, Hew, & Yew, 2015). Hence, we concluded that the data is normally distributed.…”
Section: Test Of Multivariate Assumptionsmentioning
confidence: 64%
“…The t-test was also carried out to test the differences across all the research constructs and the results also revealed that there is no significant difference (Ranganathan et al, 2011;Teo et al, 2015). Hence, the non-response bias issue does not exist in this study.…”
Section: Non-response Biasmentioning
confidence: 86%
“…Koufaris and Hampton-Sosa (2004) demonstrated that convenience is one of the contributing factors of trust regarding service usage. Convenience is specifically important for m-payment functions (Teo, Tan, Ooi, Hew, & Yew, 2015). The apparent convenience of using m-payment is its flexibility, the independence of time and space, and the level of control that consumers have over this medium.…”
Section: Perceived Benefitmentioning
confidence: 99%